The Impact of Good Governance on the Quality of Public Management Decision Making - Sari, Ade Risna (ADMAN: Journal of Contemporary Administration and Management, 2023)
Decision-making in public management is a complex and crucial process in carrying out government functions. Appropriate and effective decisions can bring positive changes to society and help achieve development goals. This study aims to analyse the impact of good governance on the quality of public management decision-making. The current research type is qualitative. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The results of the study state that Good Governance has a significant positive impact on the quality of decision-making in public management. The concept of Good Governance includes transparency, public participation, accountability, rule of law, professionalism, and technology utilisation. The implementation of Good Governance principles brings various benefits, including increased transparency, strengthened public participation, increased bureaucratic efficiency, improved quality of public services, encouraging economic growth, and creating social peace and stability.